High risk feminism in Colombia: women's mobilisation in violent contexts - Zulver, J (2018)
Against all odds, in uncertain and violent times, Colombian women are mobilising for gender justice. They do so even when they face ongoing violence and personal threats from a variety of armed actors. The questions arise: how and why do women mobilise in contexts of high violence and insecurity? Despite a well-established tradition of studying women’s social movements in times of conflict, and of high risk collective action more generally, there is a lacuna when it comes to analysing feminism as a mobilisation strategy. My research uses the case studies of the Liga de las Mujeres Desplazadas (League of Displaced Women, LMD), and AFROMUPAZ (Afro-Colombian Women for Peace) to illustrate the utility of an original framework – High Risk Feminism – to explain how and why women chose to act collectively, despite the real and threatened dangers that this implies. The thesis further looks to a similar setting (an invaded neighbourhood in Riohacha, La Guajira) where displaced women do not mobilise, in order to strengthen the parameters of the HRF framework. In all, it posits that we will see a specifically feminist type of mobilisation emerge when a leader is able to form a charismatic bond with participants by framing participation as ‘worth it’ in a domain of losses, despite the risks this incurs.